2014
DOI: 10.3390/molecules19032733
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Biological and Cytotoxic Activities of Plant Extracts and Compounds Isolated from Ferula lutea

Abstract: Abstract:The present work describes the phytochemical study on Ferula lutea flowers. Total phenolics and flavonoids of the n-butanol and ethyl acetate extracts were quantified (phenolics [40.68-52.29 mg gallic acid equivalent/g of dry weight], flavonoids [12.38-14.72 mg quercitin/g dry weight]). Two diastereoisomers were isolated and identified using spectroscopic techniques (1D, 2D NMR and GC-MS). The extracts and diastereoisomers were tested for antioxidant, antiacetylcholinesterase, antimicrobial, antidiabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In previous reports, anti-AChE activities of the ethanolic extract of F. hermonis, the methanol extract of F. assafoetida, and the ethyl acetate and n-butanol extracts of F. lutea were studied, and all extracts showed low ability for inhibiting acetylcholinesterase. [37,41,50] There is no study about anti-BChE activity of the extracts from Ferula species, so this the first study about anti-BChE activity.…”
Section: Anticholinesterase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, anti-AChE activities of the ethanolic extract of F. hermonis, the methanol extract of F. assafoetida, and the ethyl acetate and n-butanol extracts of F. lutea were studied, and all extracts showed low ability for inhibiting acetylcholinesterase. [37,41,50] There is no study about anti-BChE activity of the extracts from Ferula species, so this the first study about anti-BChE activity.…”
Section: Anticholinesterase Activitymentioning
confidence: 99%
“…Up to this time, antioxidant properties of various extracts (hexane, ethyl acetate, butanol, methanol, and ethanol) obtained from Ferula species (F. assafoetida, F. szowitsiana, F. microcolea, F. lutea, and F. hermonis) were investigated using different methods such as DPPH free and ABTS cation radical scavenging and metal chelating assays. [37][38][39][40][41] According to literature, generally the methanol extracts showed the highest antioxidant activity. The results are comparable to those of earlier studies.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Methyl 3,5‐ O ‐dicaffeoylquinate and 3,5‐ O ‐dicaffeoylquinic acid from the flower of F. lutea Poir. significantly inhibit 5‐LOX enzyme, which catalyses the dioxygenation of polyunsaturated fatty acids to produce Hydroperoxyeicosatetraenoic acids and Hydroxyeicosatetraenoic Acids . Crude extract from F. persica and isolated active ingredients, persicasulphide and umbelliprenin, significantly inhibit MMP‐2 and 9, a family of endopeptidase which regulates destruction of extra cellular matrix and is involved in inflammatory arthritis …”
Section: Finding and Resultsmentioning
confidence: 99%
“…The genus Ferula is the main source of biologically active compounds, for instance, sesquiterpenes and coumarins. Recent studies have shown potent antioxidant, apoptotic activity, and cytotoxic effects of Ferula genus, as well [10][11][12]. Also, the cytotoxic impacts of methanolic extract of F. latisecta roots have been reported in preliminary screening assays of Soltani et al research.…”
Section: Introductionmentioning
confidence: 95%